The Effect of Location of an Ingested Source in a Human Body Model on Electromagnetic Propagation - 정지현; 김세윤 (한국전자파학회, 2011)
Electromagnetic fields, radiated from an intestine-ingested source and propagated through an inhomogeneous human body model, are computed with the finite-difference time-domain (FDTD) method. The calculated results obtained at some receiving points vertically placed according to the abdomen of the human body model show unusual dip patterns in the frequency domain. The frequency of this unusual dip varies according to the location of the receiving points. Thus, the relationship between the frequency of the unusual dip and the incident angle of the line-of-sight is analyzed. The effect of the location of an ingested source on the above relationship is also investigated. The slope of the approximately linear relationship is affected by the location of the ingested source.